EKONOMI KREATIF, UPAYA MENGINGKATKAN EKONOMI DALAM PEMANFAATAN BUAH MENGKUDU MENJADI KOPI BERKHASIAT DITENGAH PANDEMI COVID-19 - Tb Dedy Fuady (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
The University of Banten Jaya (UNBAJA) Student Work Lecture Program (KKM) in 2020, amidst the prolonged Covid-19 Pandemic and has an impact on the Decrease in the Economic Sector of the Community, so this program aims to improve the skills and creativity of the community, especially Serang City in Perumahan Ciujung Damai, Kec. Kragilan, Kab. Serang, in particular. Housewives in utilizing plant products that may not be considered to have a Selling Value, namely noni fruit or in Latin (noni). The method of implementing this program is by: 1. Field observations, interviews regarding regional economic potential, 2. Providing training on how to use noni fruit to process coffee with other flavors, 3. Conduct training in the marketing aspect by making attractive packaging. The result of this activity is the use of this efficacious noni coffee fruit can improve the community's economy, and can preserve plants that we rarely encounter. With this program, it is hoped that Perumahan Ciujung Damai, Kec. Kragilan, Kab. Serang can improve their skills and creativity and increase income in the economic sector amid the COVID-19 epidemic and can also provide eco-tourism areas.